Pinkalicious : School Rules - Kann, Victoria (New York HarperCollins Publishers, 2010)
When Pinkalicious brings her imaginary unicorn, Goldie, to school and teaches him the rules, he helps her and the other students to become better friends.
Include Colour Illustrations
Keywords: Schools -- Juvenile fiction